Development of Supplementary Teaching Materials Based on Local Wisdom of The Sungai Kakap Community on Material Form, Substance, and Its Changes - Mariyam, Siti; Hairida,; Mayasari, Eni (Hydrogen: Jurnal Kependidikan Kimia, 2026)
Contextual learning is emphasized in the Independent Curriculum to help students connect scientific concepts with real-life situations. However, the integration of local wisdom into science learning materials at SMPN 1 Sungai Kakap remains limited, particularly for the topic of states of matter and their changes. This study aimed to develop supplementary science teaching materials based on the local wisdom of the Sungai Kakap community and to determine their feasibility and user responses. The study employed the ADDIE development model, limited to the analysis, design, and development stages. The participants consisted of six expert validators, including two material experts, two graphic experts, and two language experts; three science teachers; and 36 Grade VIII students. The students consisted of 12 students in a small-scale trial and 24 different students in a large-scale trial. Data were collected through interview guides, validation instruments, and teacher and student response questionnaires. The validation instruments used a four-point Likert scale, while the validity of the instruments was assessed using the Gregory coefficient. The feasibility of the developed teaching materials was evaluated based on material, graphical, and language aspects, while teacher and student responses were analyzed using percentage scores and interpreted according to predetermined criteria. The feasibility assessment resulted in percentages of 98.96% for the material aspect, 92.19% for the graphical aspect, and 98.33% for the language aspect, indicating a very feasible category. The teacher response was 92.59%, while the student responses were 91.25% in the small-scale trial and 95.21% in the large-scale trial, indicating very positive responses. These findings indicate that the developed supplementary science teaching materials based on Sungai Kakap local wisdom meet the predetermined feasibility criteria and received positive responses from teachers and students. Therefore, the materials are suitable for use as supplementary resources to support contextual science learning on states of matter and their changes.